Reverse transcription of avian myeloblastosis virus 35S RNA. Early synthesis of plus strand DNA of discrete size in reconstructed reactions. - Olsen, J C (1982)
The early DNa products of reverse transcription have been analyzed from reconstructed reactions containing avian myeloblastosis virus 35S RNA . tRNAtrp complex and highly purified reverse transcriptase. We describe conditions for the synthesis of genome-length complementary DNA and two discrete species of plus strand DNA (the same chemical polarity as the viral RNA genome) about 300 and 400 nucleotides in length. Plus DNA400 and plus DNA300 were detected by molecular hybridization with DNA probes complementary to sequences from both the 3'- and 5'-ends of the viral RNA. Both species appear to be copied from the 5'-end of minus strand DNA by their hybridization properties and their early synthesis when only the 5'-end of minus strand DNA is available as template. Restriction endonuclease mapping of plus DNA400 and plus DNA300 rules out a precursor-product relationship between the two. Rather the results suggest a unique initiation site for both species, with plus DNA400 containing internal sequences not present in plus DNA300. Plus DNA400 and plus DNA300 appear to be analogous to early plus DNA species detected in cells early after retrovirus infection. Thus, purified reverse transcriptase appears to be enzymatically sufficient for synthesis of genome-length complementary DNA and initiation and synthesis of early plus strand DNA as observed in infected cells.